Implementasi Treatment Sauna Pada Ibu Nifas Untuk Mengurangi Kecemasan Berbasis Homecare - Husnul Khatimah; Susiani Endarwati; Kurniati Akhfar; Rika Rika (PPNI UNIMMAN, 2024)
The postpartum period lasts for approximately 6 weeks, during this period postpartum mothers experience many physical and psychological changes. One of the psychological changes that postpartum mothers can experience is anxiety. Anxiety is a condition that makes people uncomfortable and uneasy because of worry. This can have an impact on the mother's breast milk production, depression has a tendency to injure itself. So alternatives need to be made to reduce maternal anxiety. Sauna is one of the traditional alternative therapy options to reduce depression, increase the mother's comfort, relax and restore the mother's mental and physical condition. The aim of implementing sauna treatment for postpartum mothers is to reduce homecare-based anxiety. The method for this activity starts with distributing brochures, interviews, implementation and evaluation. The results of the service activities carried out were able to increase the mother's sense of comfort and relaxation. Based on the results of the re-interview after implementing the Sauna Treatment, the mother stated that she felt comfortable and began to relax. The results of respondent 1's statement